2022
DOI: 10.1021/acs.macromol.1c02396
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Degradation in Thioester Cross-linked Hydrogels as a Function of Thiol Concentration, pKa, and Presentation

Abstract: Stimuli-responsive degradation of hydrogels has established and emerging utilities ranging from controlled release of biological products to sacrificial molding. Although covalent adaptable networks are particularly amenable for these applications, their degradation kinetics have yet to be clearly elucidated in these swollen material systems. In this work, the thiol−thioester exchange reaction in cross-linked poly(ethylene glycol) (PEG) hydrogels is characterized to determine the relative effects of thiol conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…We also employed a rheometer to track the degradation of SM (50 mg) in the presence of Cys (5 mM) over time and found a solution point at 560 s with storage modulus G ′ lower than loss modulus G ″, indicating the formation of a liquid solution (Figure E). The experimental results above confirmed that hydrogel SM exhibits good sensitivity/selectivity toward Cys, making it suitable for on-demand biodegradation, chemosensing, or controlled release. ,,, …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…We also employed a rheometer to track the degradation of SM (50 mg) in the presence of Cys (5 mM) over time and found a solution point at 560 s with storage modulus G ′ lower than loss modulus G ″, indicating the formation of a liquid solution (Figure E). The experimental results above confirmed that hydrogel SM exhibits good sensitivity/selectivity toward Cys, making it suitable for on-demand biodegradation, chemosensing, or controlled release. ,,, …”
Section: Resultssupporting
confidence: 55%
“…The experimental results above confirmed that hydrogel SM exhibits good sensitivity/selectivity toward Cys, making it suitable for ondemand biodegradation, chemosensing, or controlled release. 20,25,39,40 Hydrogel Systems for Controlled Drug Release. Next, we explored drug release using the degradable hydrogel.…”
Section: Table 1 Photophysical Properties For the Fluorophoresmentioning
confidence: 99%
“…Full degelation of the network occurs in the presence of a >2× molar excess of thiols (per Flory–Stockmayer statistics for step-growth networks) and nucleophilic or basic catalysts due to exchange reactions between thiols and thioesters. , To extend this concept to semicrystalline networks, tough polymerized networks were immersed in acetone containing an 8× molar excess of PETMP with respect to thioester units and 1 mol equiv of triethylamine (TEA). The 250 μm micron thick film was observed to dissolve fully over the course of several hours as thiol–thioester exchange reactions degraded the network into soluble oligomers and in accordance with previously developed kinetic models. , Subsequent solvent removal yielded a low-viscosity melt, suggesting full degelation (Figure A). Size-exclusion chromatography (SEC) confirms that network degradation produces low-molecular-weight oligomers of M N ≈ 800–2700 g mol –1 (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…The 250 μm micron thick film was observed to dissolve fully over the course of several hours as thiol−thioester exchange reactions degraded the network into soluble oligomers and in accordance with previously developed kinetic models. 68,69 Subsequent solvent removal yielded a low-viscosity melt, suggesting full degelation (Figure 2A). Size-exclusion chromatography (SEC) confirms that network degradation produces low-molecular-weight oligomers of M N ≈ 800−2700 g mol −1 (Figure 2B).…”
Section: Degradation and Repolymerizationmentioning
confidence: 99%
“…Cross-linking of the polymers is central for maintaining the structural integrity of the materials and for controlling their mechanical properties. Numerous different polymer cross-linking methods have been developed and explored for generating hydrogels, including both covalent chemistries and noncovalent strategies. The former results in hydrogels with long-term structural robustness, whereas the latter allows for dynamic remodulation of the materials by cells. Noncovalently cross-linked hydrogels are also often shear thinning, which is an attractive feature for three-dimensional (3D) bioprinting and other applications requiring syringe extrusion of the materials, such as in cell-injection therapy and soft-tissue filler treatments. …”
Section: Introductionmentioning
confidence: 99%